MammoWeb continuing medical education (CME): a Web-based breast imaging CME program...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Krebs TL; Berg WA; Roys SR; Ratakonda S; Pomerantz SM; Siegel EL (Journal of Digital Imaging)
The ubiquity of the world-wide web allows unique educational opportunities for continuing medical education (CME). We have designed a comprehensive breast imaging CME curriculum to permit individual physicians in their homes or offices to use personal computers to ease the burden of this process. Category 1 CME credits can be earned off-hours without having the physician travel out of town. In addition, since the course is computer-based, the overall costs to the participant are substantially reduced. The program can be updated on an ongoing basis to include new technology or to provide additional information requested by the users. Copyright (c) 1999 by W.B. Saunders Company